The Epistemology of scientific investigation in social sciences and humanities - Musso, Paolo (2017)
Nowadays, it seems very often that social sciences, and even more the humanities, are trapped between two opposite but equally unsatisfactory alternatives: either to conform completely to the method of natural science (which push them towards a deleterious reductionism that disregards the most characteristic properties of their objects) or to give up the ambition of being forms of true knowledge (which push them towards an equally deleterious irrationalism that turns them ineffective and therefore useless). However, a correct understanding of the experimental method, of its nature and its limits, enables us to demonstrate the full legitimacy of other forms of true knowledge besides natural science, from which these other forms differ, not in regards to their nature, but in regards to the degree of certainty they can reach, since they use different methods that are dependent on their different objects and that are neither completely identical nor completely different from the experimental method, but analogous to it.